Stock liquidity and capital structure: International evidence - Dang Tùng Lâm; Hai Ly Ho; Chi Dzung Lam; Thanh Thao Tran; Xuan Vinh Vo (Cogent Economics & Finance, 2019)
Relying on the assumption that equity market provides useful information for firm decision, this study examines the effect of stock liquidity on corporate capital structure decision. We also analyze whether this effect varies according to country-level institutional environments. Using a comprehensive international dataset of 19,939 firms across 41 countries over 2000-2010, the paper offers two key findings. First, firms with higher stock market liquidity tend to have lower leverage. Second, countries with strong institutional environments are more likely to have a weaker (negative) relationship between stock market liquidity and leverage. These results are robust to different liquidity measurement and subsamples.
Keywords: G14; G30; 330; capital decision; liquidity; institutional environment; leverage